A generalized conditional intensity measure approach and holistic ground-motion selection. - Bradley, Brendon A.
A generalized conditional intensity measure (GCIM) approach is proposed for use in the holistic selection of ground motions for any form of seismic response analysis. The essence of the method is the construction of the multivariate distribution of any set of ground-motion intensity measures conditioned on the occurrence of a specific ground-motion intensity measure (commonly obtained from probabilistic seismic hazard analysis). The approach therefore allows any number of ground-motion intensity measures identified as important in a particular seismic response problem to be considered. A holistic method of ground-motion selection is also proposed based on the statistical comparison, for each intensity measure, of the empirical distribution of the ground-motion suite with the ?target? GCIM distribution. A simple procedure to estimate the magnitude of potential bias in the results of seismic response analyses when the ground-motion suite does not conform to the GCIM distribution is also demonstrated. The combination of these three features of the approach make it entirely holistic in that: any level of complexity in ground-motion selection for any seismic response analysis can be exercised; users explicitly understand the simplifications made in the selected suite of ground motions; and an approximate estimate of any bias associated with such simplifications is obtained.
Keywords: Generalized conditional intensity measure (GCIM).; Ground-motion selection; Conditional mean spectrum (CMS).; Statistical goodness-of-fit tests; Seismic response bias